Postexercise Recovery of Schlemm’s Canal and Intraocular Pressure in Healthy Individuals: An Observational Study Using Swept-Source Optical Coherence Tomography - Mu Li; Xiaoqin Yan; Zhaoxia Luo; Hong Zhang (Journal of Ophthalmology)
Purpose. To observe the recovery process of postexercise Schlemm’s canal (SC) and intraocular pressure (IOP) in healthy individuals. Methods. Twenty healthy individuals were recruited. SC and IOP were evaluated before exercise, immediately after exercise, and 15, 30, and 60 minutes after exercise. Superior, inferior, nasal, and temporal SC quadrants were evaluated using swept-source optical coherence tomography (SS-OCT). Results. Average SC area (3726.81 ± 1167.06 vs. 4660.57 ± 1284.82 µm2) and perimeter (324.11 ± 58.95 vs. 367.19 ± 73.34 µm) increased, and IOP (14.02 ± 2.33 vs. 11.65 ± 1.90 mmHg) decreased significantly during exercise (all p<0.001). After exercise, both SC and IOP recovered to preexercise values, and the recovery time for postexercise SC dimensions (15 minutes) was shorter than that for postexercise IOP (60 minutes). After adjusting for age, gender, axial length, central corneal thickness, and spherical equivalent, postexercise changes in SC dimensions were not significantly associated with postexercise changes in IOP compared with preexercise values (all p>0.05). There were no significant differences in the observable SC proportion before and after exercise (all p>0.05). Conclusions. The exercise-induced SC expansion and IOP reduction could recover to preexercise values after exercise, and SC recovered to preexercise values ahead of IOP. Moreover, SC might be regulated by the sympathetic nerves and could be an important causative factor of changes in IOP during and after exercise.